Mitral stenosis due to rheumatic heart disease - A rare cause of massive hemoptysis. (2018) - Korzan, Sophie; Jones, Evan; Mutneja, Rahul; Grover, Prashant
Abstract: Severe mitral valve stenosis caused by rheumatic heart disease presenting initially as massive hemoptysis has become a rare occurrence in contemporary western medicine. Massive hemoptysis can be due to multiple disease processes including airway diseases such as bronchiectasis, pulmonary parenchymal disease of infectious or autoimmune etiology, pulmonary AVM's, hematologic disorders, and numerous drugs and iatrogenic injuries. It is less associated with congestion from rheumatic heart disease due to the earlier detection and subsequent management of cardiac valve disease preventing the sequela of more severe disease. We describe a case of a 59 year-old woman with hemoptysis, who was found to have severe mitral stenosis consistent with rheumatic heart disease. We demonstrate the appearance of pulmonary venous congestion can be seen on bronchoscopic examination in severe mitral stenosis and discuss the significance of the Wilkins score to help guide management.